Strategy to Revive Bandung Skywalk; Refunctional Concept of Failed City Area - Nurcahya, Yan; Syah, M Kautsar Thariq; Sugiarto, Deri; Negara, Teddiansyah Nata; Putra, Rian Ananda; Hilmayani, Syalwa Linda (Journal of Architectural Research and Education, 2026)
The purpose of this study is to provide insight to the government, society, and further researchers in reviving the Bandung Skywalk. As we know, the Skywalk or Teras Bandung is one of the icons of the City of Bandung which was built in 2017 and has become one of the tourist destinations for local people or tourists from Jabodetabek and other tourists. This study applies the use of descriptive qualitative methods with a phenomenological approach and the theory of urban spatial atmosphere. Apart from the occurrence of the Copid-19 event which has had a negative impact on life in many countries, to the point of preventing the movement or activities of people gathering or moving to public places. The Bandung Skywalk has no initial target when the city's public facilities are not functioning after Covid-19 can be resolved. With this study, we provide the concept of refunctioning the Bandung Skywalk to the Bandung City government so that it can revive and utilize public facilities better.Keywords – City Area, Refunction, Skywalk Bandung, Teras Bandung